Determining the attidute of middle school students to the physical exercises in the study of the various sections of the program - Malyshkin, A.N. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to consider the ratio of students of the middle classes to the game, to the competition, to the implementation of the training exercises, putting educational standards while studying athletics, football, basketball, volleyball and gymnastics. Material: a sociological survey involved 229 students’ grades 5-9 secondary schools of Kherson region, Novotroitsk district. Results: set a high level of interest to students of all classes of gaming method of training on physical training lessons, except gymnastics, the re-studying volleyball, basketball, competitive learning athletics, football, controlling the lessons volleyball, basketball. Conclusion: there is no clear game system for learningstudents gymnastic exercises and the study of other subjects is not enough, poor quality or missing their use during the execution of training exercises to learn techniques and tactics.